Effect of organic matter on the physical and chemical properties of the soil and the yield of purple corn (zea mays l.) in fundo Los Pichones Tacna – 2019 - Cruz Mamani, Enderson Henry (2023)
The indiscriminate use of chemical products in agriculture degrades the soil ecosystem, to mitigate this situation, it is proposed to determine the effect of organic matter on the physicochemical characteristics of the soil and the yield of purple corn (Zea mays L.), it was used the DBCA experimental design with 4 repetitions and with the following treatments: T1: INIA 615/30 t/ha EV; T2: INIA 615/40 t/ha EV; T3: INIA 615/30 t/ha ECS; T4: INIA 615/40 t/ha ECS; T5: INIA 615/200N-150P205-120K2O; T6: PMV 581/30 t/ha EV; T7: PMV 581/40 t/ha EV; T8: PMV 581/30 t/ha ECS; T9: PMV 581/40 t/ha ECS and T10: PMV 581/200N-150P205-120K2O. The analyzes showed that by incorporating organic and inorganic fertilizers the texture of the sandy loam soil remains the same, however, after a certain time, the values ​​of the physicochemical properties of the soil increase and after sowing purple corn, these values ​​decrease due to the extraction of nutrients by the crop and the transformations and reactions that occur in the soil. Regarding the production components, there are no statistical differences except for the yield variable, of high statistical significance, where the highest and lowest yield was obtained by T7 and T1 with 8,678.62 and 5,462.37 kg/ha respectively.